2019
DOI: 10.3390/pathogens8040196
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Maintenance of Tissue Resident Memory CD8+ T Cells after Viral Infection

Abstract: Tissue resident memory (TRM) CD8 T cells comprise a memory population that forms in peripheral, non-lymphoid tissues after an infection that does not recirculate into the bloodstream or other tissues. TRM cells often recognize conserved peptide epitopes shared among different strains of a pathogen and so offer a protective role upon secondary encounter with the same or related pathogens. Several recent studies have begun to shed light on the intrinsic and extrinsic factors regulating TRM. In addition, work is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…While CD103 is often considered a canonical T RM marker, it is not universally expressed on T RM in all tissue compartments; for example, in the lungs, its expression can vary between the epithelium and parenchyma. [ 17,29 ] Other adhesion molecules that may serve a similar purpose include CD49a (VLA‐1) and LFA‐1. [ 5,28 ]…”
Section: Tissue‐resident T Cell Biologymentioning
confidence: 99%
“…While CD103 is often considered a canonical T RM marker, it is not universally expressed on T RM in all tissue compartments; for example, in the lungs, its expression can vary between the epithelium and parenchyma. [ 17,29 ] Other adhesion molecules that may serve a similar purpose include CD49a (VLA‐1) and LFA‐1. [ 5,28 ]…”
Section: Tissue‐resident T Cell Biologymentioning
confidence: 99%
“…clearing influenza virus 36 – 48 hours faster after re-infection ( 18 , 26 ). Both CD4 + and CD8 + Trm are established after influenza virus infection in mice and based on various surface markers different subsets can be distinguished ( 26 28 ). The following three subsets of CD8 + CD69 + lung-resident memory T cells have been described based on surface expression of integrins CD49a and CD103: CD103 + CD49a - epithelial effector Trm (eeTrm), CD103 + CD49a + epithelial Trm (eTrm) and CD103 - CD49a + interstitial Trm (iTrm) ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both CD4 + and CD8 + Trm are established after influenza virus infection in mice and based on various surface markers different subsets can be distinguished ( 26 28 ). The following three subsets of CD8 + CD69 + lung-resident memory T cells have been described based on surface expression of integrins CD49a and CD103: CD103 + CD49a - epithelial effector Trm (eeTrm), CD103 + CD49a + epithelial Trm (eTrm) and CD103 - CD49a + interstitial Trm (iTrm) ( 28 ). The subsets are proposed to reside at different locations in the lung tissue with iTrm in the interstitium, eeTrm within the respiratory epithelium and eTrm in the respiratory epithelium in contact with the basement membrane ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cell population has been shown to be important against secondary encounters with a previously seen pathogen. However, many questions remain regarding our understanding of this unique cell subset and its role during influenza infections [5]. Previously, Sant's laboratory has demonstrated that CD 4 T cells specific for epitopes derived from HA are the most effective in providing help for the HA-specific B cell responses to infection and vaccination.…”
mentioning
confidence: 99%